2012
DOI: 10.1089/jwh.2012.3634
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Apples and Pears: Women's Perceptions of Their Body Size and Shape

Abstract: Background: Obesity is a growing public health problem among reproductive-aged women, with consequences for chronic disease risk and reproductive and obstetric morbidities. Evidence also suggests that body shape (i.e., regional fat distribution) may be independently associated with risk, yet it is not known if women adequately perceive their shape. This study aimed to assess the validity of self-reported body size and shape figure drawings when compared to anthropometric measures among reproductive-aged women.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 35 publications
1
12
0
2
Order By: Relevance
“…Validation studies of similar populations have found that women tend to underestimate these measurements, though secondary analyses among women who used a tape measure in our cohort produced similar results. Tendency to gain weight was also not verified, but one study found that self‐reported female body shape was consistent with anthropometric measures used to assess fat distribution. Exposure misclassification in this study is expected to be nondifferential and bias associations for the extreme categories toward the null.…”
Section: Commentmentioning
confidence: 99%
“…Validation studies of similar populations have found that women tend to underestimate these measurements, though secondary analyses among women who used a tape measure in our cohort produced similar results. Tendency to gain weight was also not verified, but one study found that self‐reported female body shape was consistent with anthropometric measures used to assess fat distribution. Exposure misclassification in this study is expected to be nondifferential and bias associations for the extreme categories toward the null.…”
Section: Commentmentioning
confidence: 99%
“…The anthropometric exposures captured are body mass index (BMI; current height and weight), most and least weighed since age 18, somatotype by age range ( 64 ), and body shape by age range ( 65 ). Current BMI has been shown to be inversely associated with endometriosis ( 66 ) and validly measured by self-reported questionnaire ( 67 69 ).…”
Section: Resultsmentioning
confidence: 99%
“…This finding suggests that girls rely more on WC than BMI when forming their body perception, possibly because WC is more clearly related to abdominal fat and changes in body shape at different ages. The focus on body parts other than the parameters of weight and height and body shape may reflect current physical ideals, as suggested by other studies (96,97). Bergström et al found that adolescents (without anorexia nervosa) overestimated their body size, particularly at the waist, buttocks and thighs (96).…”
Section: …With Actual Body Measuresmentioning
confidence: 86%